2016
DOI: 10.1016/j.ejso.2016.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and preliminary effectiveness of a physical exercise training program during neoadjuvant chemoradiotherapy in individual patients with rectal cancer prior to major elective surgery

Abstract: This pilot demonstrated that a supervised outpatient physical exercise training program for individual patients with locally advanced resectable rectal cancer during NACRT is feasible for a large part of the patients, safe and seems able to prevent an often seen decline in physical fitness during NACRT. A larger study into the cost-effectiveness of this approach is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
103
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 30 publications
3
103
1
Order By: Relevance
“…In cancer patients, PA has been shown to improve health‐related QOL and symptom burden. PA resulted in improved treatment tolerance and is associated with improved PFS and OS , suggesting that the benefit of PA is not confined to disease‐free survivors.…”
Section: Intervention For Pawlmentioning
confidence: 99%
“…In cancer patients, PA has been shown to improve health‐related QOL and symptom burden. PA resulted in improved treatment tolerance and is associated with improved PFS and OS , suggesting that the benefit of PA is not confined to disease‐free survivors.…”
Section: Intervention For Pawlmentioning
confidence: 99%
“…The primary type of activity used in prehabilitation for patients undergoing major abdominal surgery is that which is directed to stressing the aerobic system. The most common aerobic exercises are cycling and walking, though a number of supervised programmes have used running, cycling, rowing, climbing stairs, and cross-training activities [2]. These aerobic exercises are often performed for at least 30 minutes in either a supervised or home setting from 2-7 times per week [14][15][16][17].…”
Section: Related Workmentioning
confidence: 99%
“…After major abdominal surgery, there is a significantly increased number of metabolic demands on the body [1]. The level of aerobic fitness prior to surgery has been identified as an important factor for determining the ability to cope with these increased demands and postoperative outcomes [2]. To address fitness issues, several hospitals have developed exercise (prehabilitation) programmes to improve the aerobic capacity of this patient group prior to surgery [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent systemic review identified three studies, which investigated the effect of a structured exercise programme during and after neoadjuvant chemoradiotherapy on post treatment physical fitness. The authors demonstrated that prehabilitation programme during and after neoadjuvant therapy is feasible and safe with high compliance rate [22][23][24]. Furthermore, the authors found that after completion of the exercise programme, physical fitness returned to baseline levels before chemoradiotherapy.…”
mentioning
confidence: 93%